2018
DOI: 10.1057/s41308-018-0059-3
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Structure of Immigration to the OECD: What Welfare Effects on Member Countries?

Abstract: HighlightsThe skill and origin-mix of immigration to the OECD has evolved over time; especially, the last wave of immigration in the post-crisis period (2010)(2011)(2012)(2013)(2014)(2015) is different in terms of skill and origin structure from the previous waves.We explore the welfare implication of this changing structure for native OECD citizens in terms of wages, employment, fiscal (i.e., public spending and taxes) and market size effects (i.e., the increased economies of scale and variety in consumption)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…endogenous firms' creation and number of varieties available to consumers). This finding is in line with the quantitative findings of di Giovanni et al (2015), Aubry et al (2016), andBurzy ński et al (2018), and with the recent empirical results of Beerli et al (2021).…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…endogenous firms' creation and number of varieties available to consumers). This finding is in line with the quantitative findings of di Giovanni et al (2015), Aubry et al (2016), andBurzy ński et al (2018), and with the recent empirical results of Beerli et al (2021).…”
Section: Introductionsupporting
confidence: 92%
“…Others endogenize labor supply decisions while disregarding involuntary unemployment (e.g. Aubry et al, 2016;Docquier et al, 2010;Storesletten, 2000), or treating it as exogenous (Burzy ński et al, 2018;Docquier et al, 2014). Finally, some studies endogenize unemployment responses as the outcome of a search-and-matching process instead of relying on a competitive wage determination framework (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We account for the difference in employment rates between groups by introducing heterogeneity in the preference parameters in the utility functions in equation ( 9). Labor force data reveal that differences in employment rates are mainly governed by differences in participation rates (Burzynski et al, 2018). This motivates our choice to endogenize participation rates and disregard involuntary unemployment.…”
Section: Alternative Labor Market Structuresmentioning
confidence: 99%
“…The latest wave of immigration in the post-crisis period (2010-2015) is unlike previous waves in terms of skill and origin structure. Burzynski, Docquier, & Rapoport (2018) have shown that the welfare effects of immigration are very heterogeneous across skill groups, countries of destination, and immigration waves. For instance, the latest wave period of immigration is less skilled and brings fewer benefits.…”
Section: Introductionmentioning
confidence: 99%